The Role of Ethical Leadership in Psychological Capital and Job Satisfaction of Immigrant Workers: Evidence From the Hotel Industry of Cyprus - Salih Katircioglu; Huseyin Arasli; Mehmet Necati Cizreliogullari (SAGE Open, 2022)
The goal of this research is to figure out the moderating act of ethical leadership on the effects of job satisfaction and psychological capital of employees. The Hotel industry in Northern Cyprus has been preferred with this respect. The study was conducted within the appropriate literature. Research-oriented data collection tools designed and used in accordance with the purposes of the research, research questions and hypotheses are surveyed. The findings of the study revealed the moderating role of ethical leadership (EL) on psychological capital (PsyCap) and job satisfaction (JS). It was also found that the participants were on the idea of working under equal conditions adopted via ethical leadership factors. The current study is a new era for the developmental issues of hospitality in terms of management and it is hoped that it will yield basic basements for further studies.